Prevalence of use of preimplantation genetic diagnosis in Unidade Clínica de Paramiloidosefrom Centro Hospitalar do Porto - Valdrez, K (2014)
Introduction: The Familial Amyloid Polyneuropathy, with the world’s largest focus in Portugal, is recognized by the National Board of Assisted Reproductive Technologies as a serious disease eligible for Preimplantation Genetic Diagnosis. This study aims to determine the prevalence of the use of Preimplantation Genetic Diagnosis in FAP carriers followed in Unidade Clínica de Paramiloidose, Centro Hospitalar do Porto, and to identify the associated factors. Material and Methods: Between January and May 2013, a representative sample of Portuguese Familial Amyloid Polyneuropathy carriers, aged between 18 and 55 years, was systematically recruited. The analysis is based on 111 carriers with previous familial diagnosis, who reported having ever tried to get pregnant after 2001. Data on sociodemographic characteristics and use of Preimplantation Genetic Diagnosis were collected through a self-administered questionnaire. Proportions were compared using the chi-square test. Crude and adjusted odds ratios (OR) and the respective confidence intervals of 95% (95% CI) were estimated using multivariate logistic regression. Results: The prevalence of use of Preimplantation Genetic Diagnosis was 20.7% (95% CI: 13.6-29.5). After adjustment, a household income above 1000 €/month (OR = 11.87; 95% CI 2.87-49.15) was directly associated with the use of Preimplantation Genetic Diagnosis, while carriers with an individual diagnosis (OR = 0.15; 95% CI 0.04-0.57) and children born after 2001 (OR = 0.07; 95% CI 0.02-0.32) revealed a prevalence of use significantly lower than those with a individual diagnosis and children born before 2001. Discussion: The low prevalence of use of Preimplantation Genetic Diagnosis, as well as the less frequent use of the technique by those with a lower household income, shows the importance of improving access to Preimplantation Genetic Diagnosis in the case of Familial Amyloid Polyneuropathy. Conclusion: This work contributes to increase the sensitivity of health professionals around the use and accessibility to Preimplantation Genetic Diagnosis among Familial Amyloid Polyneuropathy carriers.